2008
DOI: 10.1007/s11270-008-9744-6
|View full text |Cite
|
Sign up to set email alerts
|

Lead Bioaccessibility in Soil and Mine Wastes After Immobilization with Phosphate

Abstract: The immobilization of lead by the reaction with phosphate bearing materials is a promising remediation method for contaminated soils. Low soluble neo-formed lead-phosphate phases similar to chloropyromorphite [Pb 5 (PO 4 ) 3 Cl], can control availability and mobility of lead in the environment, and consequently reduce human exposure, if soils are the main contamination pathway. We used three phosphate source materials [NaH 2 (PO 4 ) 3 , commercial superphosphate and phosphate rock] to study lead immobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 60 publications
0
20
0
2
Order By: Relevance
“…The following additional references have been reported since 1998: Ma and Rao 1999;Cao et al 2002;Chen et al 2003;Bolan et al 2003;Lin et al 2005;Bosso et al 2008;Miretzky and Fernandez 2009. In general, WSP fertilizers (e.g., SSP and TSP) are more effective than PR in reducing soluble Pb content in the Pb-contaminated soils because of their higher water solubility and their ability to react with Pb to form more stable Pb-P compounds.…”
Section: Concentrations Bmentioning
confidence: 99%
“…The following additional references have been reported since 1998: Ma and Rao 1999;Cao et al 2002;Chen et al 2003;Bolan et al 2003;Lin et al 2005;Bosso et al 2008;Miretzky and Fernandez 2009. In general, WSP fertilizers (e.g., SSP and TSP) are more effective than PR in reducing soluble Pb content in the Pb-contaminated soils because of their higher water solubility and their ability to react with Pb to form more stable Pb-P compounds.…”
Section: Concentrations Bmentioning
confidence: 99%
“…However, in the small intestinal phase, SSP appears to be the least effective amendment. Bosso et al (2008) used the NaH 2 (PO 4 ) 3 , super-phosphate and phosphate rock to immobilize Pb in soil and assessed the risk with the bioaccessibility tests. The results showed that the most efficient phosphate source was NaH 2 PO 4 , which reduced Pb solubility to 92% in gastric conditions after the first month of incubation.…”
Section: Bioaccessibility Of As and Pb In Soilmentioning
confidence: 99%
“…Oral bioaccessibility test, which is a measure of solubility of heavy metal in the gastrointestinal compartment, is applicable to the soil ingestion pathway (Beak et al 2006;Ruby et al 1996). The bioaccessibility of metal has also been used to evaluate the effectiveness of heavy metal remediation in soils (Bosso et al 2008;Sarkar et al 2007). Bosso's (2008) study showed that the most efficient phosphate source was NaH 2 PO 4 , which reduced Pb solubility by 92% in acidic gastric conditions after the first month.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre as atividades industriais, destaca-se a metalúrgica de metais pesados, que produz grandes quantidades de rejeitos ricos nesses poluentes (AMARAL SOBRINHO et al, 1998;BOSSO;ENZWEILER;ANGÉLICA, 2008 , 1997). Em 1995 a mineradora encerrou suas atividades deixando a céu aberto, sem nenhuma proteção, cerca de 177.000 t de resíduos de beneficiamento de Pb (EYSINK, 1988;CASSIANO, 2001 Os solos possuem características únicas quando comparados aos outros componentes da biosfera, pois se apresentam não apenas como um dreno para contaminantes, mas também como tampão natural que controla o transporte de elementos químicos e outras substâncias para a atmosfera, hidrosfera e biota (KABATA-PENDIAS;PENDIAS, 2001).…”
Section: Introductionunclassified